Direct comparison of the aging and memory effects of magnetic nanoclusters and nanoparticles - Sankar, C. Raj; Vijayanand, S.; Verma, Seema; Joy, Pattayil Alias (Solid State Communications, 2007)
The magnetic characteristics of a dense magnetic nanoparticle system and a spin glass system consisting of magnetic nanoclusters are compared. Zero field cooled and field cooled magnetization measurements, including aging and memory experiments, of the nanoparticle and the magnetic cluster systems show similar characteristics, suggesting a common origin for the spin glass-type behavior of the magnetic nanoparticle and nanocluster systems. (C) 2006 Published by Elsevier Ltd.
Keywords: Magnetic nanoparticles; magnetic properties; spin glasses

Magnetic and Mossbauer spectroscopic studies of NiZn ferrite nanoparticles synthesized by a combustion method - Sreeja, V.; Vijayanand, S.; Deka, Sasanka; Joy, Pattayil Alias (Hyperfine Interactions, 2008)
The properties of nanocrystalline Ni(0.5)Zn(0.5)Fe(2)O(4) synthesized by an auto-combustion method have been investigated by magnetic measurements and Mossbauer spectroscopy. The as-synthesized single phase nanosized ferrite powder is annealed at different temperatures in the range 673-1,273 K to obtain nanoparticles of different sizes. The powders are characterized by powder X-ray diffraction, vibrating sample magnetometer, transmission electron microscopy and Mossbauer spectroscopy. The as-synthesized powder with average particle size of similar to 9 nm is superparamagnetic. Magnetic transition temperature increases up to 665 K for the nanosized powder as compared to the transition temperature of 548 K for the bulk ferrite. This has been confirmed as due to the abnormal cation distribution, as evidenced from room temperature Mossbauer spectroscopic studies.
Keywords: Ferrite; magnetic properties; Mossbauer spectroscopy; Nanoparticles

Photocatalytic decomposition of methylene nanocrystalline titania prepared by different blue on methods - Ramaswamy, Veda; Jagtap, Neelam; Vijayanand, S.; Bhange, Deu S.; Awati, Preeti (Materials Research Bulletin, 2008)
Nanocrystalline particles of pure anatase titania were prepared by two different methods. One is the sol-gel method at ambient temperature using ultrasonication (TiO2-SG-US) and conventional stirring method (TiO2-SG-S) and the other by surfactant assisted hydrothermal synthesis (TiO2-HT). More uniform distribution/dispersion of the nanoparticles (SEM), marginally higher surface area, better thermal stability and phase purity are some of the advantages of preparation of nanocrystalline titania by sol gel ultrasonication method and hydrothermal synthesis method. The behavior of anatase titania in photocatalytic decomposition of methylene blue in aqueous medium was studied as a function of the method of preparation and the crystallite size. The nanoparticles prepared by ultrasonication method were more effective than both, the sample prepared by conventional stirring method and commercial Degussa P-25. The higher photocatalytic activity of TiO2-SG-US is attributed to the more uniform size of the particles as compared to TiO2-SG-S samples. Both TEM and XRD data on TiO2-HT samples reveal a uniform and nanocrystalline TiO2 particles, which showed photocatalytic activity in both UV and visible region although brookite phase was also present. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Catalytic properties; Nanostructures; Sol-gel chemistry

Ferromagnetic to spin glass cross over in (La,Tb)(2/3)Ca1/3MnO3 - Sankar, C. Raj; Vijayanand, S.; Joy, Pattayil Alias (Solid State Sciences, 2009)
In the series La2/3-xTbxCa1/3MnO3, it is known that the compositions are ferromagnetic for smaller values of x and show spin glass characteristics at larger values of x. Our studies on the magnetic properties of various compositions in the La2/3-xTbxCa1/3MnO3 series show that the cross over from ferromagnetic to spin glass region takes place above x approximate to 1/8. Also, a low temperature anomaly at 30 K, observed in the ac susceptibility curves, disappears for compositions above this critical value of x. A mixed phase region coexists in the narrow compositional range 0.1 <= x <= 0.125, indicating that the ferromagnetic to spin glass cross over is not abrupt. (C) 2008 Elsevier Masson SAS. All rights reserved.
Keywords: Ferromagnetism; Magnetic clusters; Manganites; perovskite; Spin glass

Magnetic characteristics of nanocrystalline multiferroic BiFeO3 at low temperatures - Vijayanand, S.; Mahajan, Mangesh B.; Potdar, H. S.; Joy, Pattayil Alias (Physical Review B, 2009)
The magnetic characteristics of nanocrystalline BiFeO3 with average crystallite sizes of similar to 50 and similar to 100 nm are evaluated by studying the temperature and field dependence of magnetization at low temperatures. Different properties such as magnetization, coercivity, and remanence show evidence for changes in the magnetic properties associated with the phase transitions at low temperatures, reported from Raman studies. Detailed field-cooled and zero-field-cooled magnetization measurements show that the likely origin of the changes in the magnetic characteristics is from the changes in the domain structure.
Keywords: bismuth compounds; coercive force; crystallites; magnetic domains; magnetic transitions; Multiferroics; Nanostructured materials; Raman spectra; remanence

Origin of high room temperature ferromagnetic moment of nanocrystalline multiferroic BiFeO3 - Vijayanand, S.; Potdar, H. S.; Joy, Pattayil Alias (Applied Physics Letters, 2009)
Single phase nanocrystalline BiFeO3 of average crystallite size similar to 25 nm with very high magnetization at room temperature is synthesized by an autocombustion method. Magnetic measurements above room temperature show deviation between field cooled and zero field cooled magnetization below 645 K, the Neel temperature (T-N) of the bulk material, indicating intrinsic nature of ferromagnetism. However, observation of a broad magnetic transition above T-N of BiFeO3 and extended up to 800 K suggests the presence of Fe3O4 as a possible magnetic impurity phase. Evidence for the presence of Fe3O4 is obtained from detailed analysis of the powder x-ray diffraction pattern.
Keywords: bismuth compounds; Combustion synthesis; crystallites; ferromagnetic materials; high-temperature effects; magnetic impurities; Magnetic moments; Magnetisation; Multiferroics; Nanostructured materials; Neel temperature; X-ray diffraction

Simple chemical co-precipitation/calcination route for the synthesis of simulated synroc-B and synroc-C powders - Potdar, H. S.; Vijayanand, S.; Mohaideen, Kamal Khaja; Patil, K. R.; Joy, Pattayil Alias; Madhavan, R. Raja; Kutty, K. V. G.; Ambashta, Ritu D.; Wattal, P. K. (Materials Chemistry and Physics, 2010)
A simple chemical co-precipitation/calcination route was developed for the synthesis of simulated synroc-B and synroc-C powders using mostly nitrate salts as starting chemicals and 20% ammonia solution as precipitant. In this route, a mixed solution containing Al-nitrate, Ca-nitrate, Ba-nitrate, zirconyl nitrate and titanyl nitrate in the molar proportion required for synroc-B is added to dilute ammonia solution to precipitate these cations in the form of their hydroxides at room temperature by maintaining pH approximate to 10.5 during precipitation. Formation of a major fluorite phase with minor amounts of anatase, rutile and hollandite phases is observed in the powder obtained after calcination in air at 750 degrees C. Multiphase crystalline synroc-B matrix containing hollandite, perovskite, zirconolite, and rutile phases is obtained after sintering the heat treated powder in the form of pellets at 1230 degrees C for 4h in air. Similarly, pure synroc-C phases with 14 and 20% simulated waste loadings were synthesized following the same synthesis protocol. These pre-treated powders with a high surface area of similar to 25 m(2) g(-1) gave sintered ceramics having density of similar to 90% for 14 and 20% waste loadings. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Oxides; Sintering

Porous Co3O4 nanorods as superior electrode material for supercapacitors and rechargeable Li-ion batteries - Vijayanand, S.; Kannan, Ramaiyan; Potdar, H. S.; Pillai, V. K.; Joy, Pattayil Alias (Journal of Applied Electrochemistry, 2013)
Porous aggregated nanorods of Co3O4 with a surface area of similar to 100 m(2) g(-1) synthesized without using any templates or surfactants give very high specific capacitance of similar to 780 F g(-1) when used as electrode in a faradaic supercapacitor, with a cycle life of more than 1,000 cycles. Further, in Li-ion batteries when used as an anode, the Co3O4 nanorods achieved a capacity of 1155 mA h g(-1) in the first cycle and upon further cycling it is stabilized at 820 mA h g(-1) for more than 25 cycles. Detailed characterization indicated the stability of the material and the improved performance is attributed to the shorter Li-insertion/desertion pathways offered by the highly porous nanostructures. The environmentally benign and easily scalable method of synthesis of the porous Co3O4 nanorods coupled with the superior electrode characteristics in supercapacitors and Li-ion batteries provide efficient energy storage capabilities with promising applications.
Keywords: Cobalt oxide; Electrode materials; Li-ion battery; Porous nanostructures; supercapacitor